Pengurusan Rangkaian : Analisis Tahap Kesihatan Rangkaian Komputer UUM Berasaskan Analisis Paket - Rosmadi, Bakar (2001)

(untitled)
Network existed long before computers became a reality. In 1846 Samuel F.B. Morse invented the digital code, in 1876 Alexander Graham Bell registered the telephone patent and in 1878 the first voice network was established. In the nineteen seventies IBM introduced the computer network which was based on the mainframe host known as SNA while Zerox introduced the concept of Ethernet. The utilization of computer network has increasingly become a necessity in line with the development of internet technology. Today every computer needs to be connected to the computer network system . With this network, varieties of information and sources can be shared. For certain sectors such as industrial, banking, business, telecommunication and security, computer network is the catalyst to their activities. If the network system fails to function, their operations will be crippled. Thus, efficient network management needs to be introduced so that network configuration can be executed accurately and management of defects can be carried out effectively in order that the network performance can be maintained at a satisfactory level. One of the methods to manage the network is to analyze the network system based on the packet analysis or protocol analysis. Through this method or protocol, several phenomena can be identified. This study aims to analyze the Northern University of Malaysia Computer Network System(1SLb.N). The objective of the study is to provide packet capture through ISLAN computer network in order to identify packet types based on delivery protocol, types of packet such as size and format, packet which cause congestion in the network, methods of packet delivery, packet which are generated and passed through the network at certain times such as low, moderate and peak utilization periods. It also aims to identify the packet generated by the system itself for the purpose of activating the system by certain protocol, surveying the packet route and measuring the utilization of the bandwidth. The analysis uses Sniffer Pro software for capture analysis. The study reveals that there are differences in the number of packet among certain utilization periods, work days and holidays, student and staff VLAN segments. Nevertheless there are no obvious differences among the various locations. A large number of packet are sent through broadcast from other segments and distributed to the whole network which involved network bandwidth. However, the bandwidth used by the system is very low. Based on the packet analysis, description of the network fitness level is done and the information obtained will help identify ways to solve the related problems.